It's mine, that's why I speak: Destination brand psychological ownership as a mediator of the link between social media brand engagement and local residents' voice behavior - David Amani (Cogent Business & Management, 2022)
Local residents' voices have been regarded as the most important extra-role behavior that determines the growth and survival of tourist destinations. This study examines the antecedents of such crucial extra-role behaviors of local residents. Furthermore, it examines the mediation role of destination brand psychological ownership in the relationship between social media brand engagement and local residents' voice behavior. The study collected data from 376 local residents and was analyzed using Structural Equation Modelling. The findings suggest that social media brand engagement plays a crucial role in motivating voice behavior among local residents. In addition, destination brand psychological ownership is a mediator of the relationship between social media brand engagement and local residents' voice behavior. Therefore, Destination Marketing Organizations (DMOs) should deliberately consider Web 2.0 technologies as strategic assets to engage local residents in enhancing brand-building behaviors through voice behavior.
Keywords: 650; destination brand psychological ownership; local residents; social media brand engagement; tourist destinations; voice behavior